Quantification of the anti-influenza drug zanamivir in plasma using high-throughput HILIC––MS/MS. (January 2011) - Lindegardh, Niklas; Hanpithakpong, Warunee; Kamanikom, Benjamas; Farrar, Jeremy; Hien, Tran Tinh; Singhasivanon, Pratap; White, Nicholas J; Day, Nicholas P J
Background: Parenteral zanamivir is a promising drug for the treatment of severe influenza. However, quantification of this polar drug in biological matrices has traditionally been difficult and the methods developed have been relatively insensitive.Results: A high-throughput bioanalytical method for the analysis of zanamivir in human plasma using SPE in the 96-well plate format and LC coupled to positive MS/MS has been developed and validated according to US FDA guidelines. The method uses 50 µµl of plasma and covers a large working range from 1––50, 000 ng/ml with a LOD of 0.50 ng/ml.Conclusion: This new LC––MS/MS assay is more sensitive than previous methods despite using a small plasma volume sample. It is particularly suitable for clinical studies on both parenteral and inhaled zanamivir.